Mike Shepherd, When Brave Men Shudder: The Scottish Origins of Dracula. Newcastle upon Tyne: Wild Wolf Publishing, 2018, 244 pp. £12.99 paper ISBN: 978-1907954696. Issue 1 (2019) - Senf, Carol
No abstract available